Risk Management of Goods and Services Procurement at PT XYZ - Andika, Ridho Erfan; Priyarsono, D. S; Jahroh, Siti (Dinasti International Journal of Economics, Finance & Accounting, 2024)
PT. XYZ is a foreign investment company engaged in the manufacturing industry of building materials. The products produced by PT. XYZ are concrete wall bricks that adhere to Japanese Industrial Standards (JIS), and have also received SNI product testing certification. In its business processes, PT. XYZ requires supplies of goods and services. The procurement implementation at PT. XYZ applies a “procurement by user” model. Risks may occur in this process, such as a lack of transparency in the supplier selection process, procurement cost constraints, and insufficient professionalism in the receipt of goods or services. ISO 31000 can serve as a guideline for implementing risk management, and the method used in this research is the House of Risk (HOR). HOR Phase 1 will produce an output in the form of Aggregate Risk Potential (ARP), which determines the priority of risk agents that will undergo further action, along with an analysis using a Pareto diagram. Followed by HOR Phase 2, which will produce outputs in the form of the difficulty level of mitigation processes (Dk) and Total Effectiveness of Difficulty Level (ETDk), determining the effectiveness ratio of each mitigation action. In this research, 18 risk events and 17 risk agents were identified, with 2 priority risk agents that will receive mitigation actions. Through HOR Phase 2, five recommendations for mitigation actions were obtained, with the top-ranking recommendation being the establishment of Standard Operating Procedures (SOP) for the procurement process